Effects of the UK Departure from UE on the Art and Culture Sector - Ana-Corina Dimitriu (Chișcareanu); Gheorghe Hurduzeu (Journal of Danubian Studies and Research, 2020)
Shadowed by the pandemic effects, BREXIT started on 1 January 2020 with a transition period and will have its full effects on 1 January 2021. Although it is too early to measure the effect of BREXIT, at the end of 2020 the art world had signals of the potential difficulties might incur. The article's objective is to identify what effects will have BREXIT on the European art market, considering the role of the UK in the global and European art world.